Infiltration of inflammatory macrophages and neutrophils and widespread pyroptosis in lung drive influenza lethality in nonhuman primates. - Jacqueline Corry (PLoS Pathogens, 2022)
Severe influenza kills tens of thousands of individuals each year, yet the mechanisms driving lethality in humans are poorly understood. Here we used a unique translational model of lethal H5N1 influenza in cynomolgus macaques that utilizes inhalation of small-particle virus aerosols to define mechanisms driving lethal disease. RNA sequencing of lung tissue revealed an intense interferon response within two days of infection that resulted in widespread expression of interferon-stimulated genes, including inflammatory cytokines and chemokines. Macaques with lethal disease had rapid and profound loss of alveolar macrophages (AMs) and infiltration of activated CCR2+ CX3CR1+ interstitial macrophages (IMs) and neutrophils into lungs. Parallel changes of AMs and neutrophils in bronchoalveolar lavage (BAL) correlated with virus load when compared to macaques with mild influenza. Both AMs and IMs in lethal influenza were M1-type inflammatory macrophages which expressed neutrophil chemotactic factors, while neutrophils expressed genes associated with activation and generation of neutrophil extracellular traps (NETs). NETs were prominent in lung and were found in alveolar spaces as well as lung parenchyma. Genes associated with pyroptosis but not apoptosis were increased in lung, and activated inflammatory caspases, IL-1β and cleaved gasdermin D (GSDMD) were present in bronchoalveolar lavage fluid and lung homogenates. Cleaved GSDMD was expressed by lung macrophages and alveolar epithelial cells which were present in large numbers in alveolar spaces, consistent with loss of epithelial integrity. Cleaved GSDMD colocalized with viral NP-expressing cells in alveoli, reflecting pyroptosis of infected cells. These novel findings reveal that a potent interferon and inflammatory cascade in lung associated with infiltration of inflammatory macrophages and neutrophils, elaboration of NETs and cell death by pyroptosis mediates lethal H5N1 influenza in nonhuman primates, and by extension humans. These innate pathways represent promising therapeutic targets to prevent severe influenza and potentially other primary viral pneumonias in humans.